Monitoring Antiretroviral Therapy in HIV-Infected Children in Resource-Limited Countries: A Tale of Two Epidemics - Elijah Paintsil (AIDS Research and Treatment)
Twenty-nine years into the HIV epidemic, several advances have been made; however, there remain several challenges particularly with pediatric HIV in resource-limited countries. The obstacles facing pediatric antiretroviral therapy (ART) delivery in resource-limited countries are multifaceted: lack of health care infrastructure, limited availability of pediatric drug formulations, lack of early HIV diagnostic and monitoring techniques, limited manpower with expertise in pediatric HIV care, limited donor funding, and competing public health priorities with limited health care budget. In this paper, the challenges with various ART monitoring tools in resource-limited countries are discussed. Noninvasive (e.g., patient, clinical events outcome, and adherence) and invasive (e.g., immunologic and virologic) monitoring tools are discussed. Several cheap and technically less complex laboratory tests for monitoring are becoming available. Funding agencies and country programs should invest in validating the use of current technologies to optimize pediatric HIV care in resource-limited countries.